Patients' insights into unused medications during the COVID-19 outbreak: A qualitative study - Mutaseim Makki; Asrul Akmal Shafie; Ahmed Awaisu; Rabia Hussain; Moza Al Hail; Walid Mohammed ElMotasim; Mohamed Yousif Mohamed Ali Taha; Einas Abdoun; Noriya Mohd J. Al-Khuzaei; Gamila Salama; Abdulrouf Pallivalapila; Wessam El Kassem; et al. (Exploratory Research in Clinical and Social Pharmacy)
Background: The COVID-19 outbreak had significant global healthcare implications, including the use of medications. This is specifically evident in the surge in use of some medication and a decline in the use of others. As a result, some medications end up unused, which may have subsequent health, economic, and environmental impacts. Aim: To explore patients' insights into unused medications during the COVID-19 outbreak. Materials and methods: Semi-structured interviews were conducted with 30 patients attending various public and private healthcare facilities in Qatar between January and July 2021. A thematic analysis approach was utilized, with 2 researchers independently analyzing, comparing, and discussing the coding. The resulting themes were further discussed in research group meetings until a consensus was reached. Results: Seven themes emerged: awareness of unused medications and their impacts on health, economy, and the environment; barriers contributing to nonadherence/unused medications; sources of medications; factors facilitating medication use; patients' behaviors toward donated medications/reuse; patients' awareness of medication storage requirements; and patients' desire to appropriately dispose of unused medications. Conclusion: The COVID-19 outbreak disrupted medication supply and adherence, resulting in an increase in unused medications and inappropriate disposal. Adherence is crucial for improving patients' health and preserving medications. Implementing mail-return systems for unused medications could be a viable solution during disease outbreaks.